Evaluation of 25% Poloxamer As a Slow Release Carrier for Morphine in a Rat Model - Sulimai, Nurul H.; Ko, Jeff C.; Jones-Hall, Yava L.; Weng, Hsin-Yi; Deng, Meng; Breur, Gert J.; Knipp, Gregory T. (Frontiers in Veterinary Science, 2018)
The objectives of this study were to evaluate poloxamer as a slow release carrier for morphine (M) and potential tissue irritation after subcutaneous (SC) poloxamer-morphine (PM) injection in a rat model. Based on the result of a previous in vitro work, 25% poloxamer, with and without morphine, and saline were administered in 14 rats’ flanks. Blood for morphine concentrations was automatically sampled at multiple preprogrammed time points using the CulexTM unit for 48 hours. Skin tissues from the injection sites were harvested and evaluated for histopathological changes. Following M or PM administration, it was determined that the half-life (t½) was significantly longer in the PM (5.5 ±7.2 hr) than M (0.7± 0.8 hr) indicated a slow dissolution of poloxamer with morphine. The tmax was within 15 minutes and Cmax was approximately 3 times higher with M than with PM, reaching 716.8 (±153.7 ng/ml) of plasma morphine concentrations. There was no significant difference in total area under the curve and clearance of M vs PM. Histology inflammatory scores were similar between M, PM, and poloxamer but were significantly higher than saline control. We concluded that 25% poloxamer was capable of increasing the t½ of morphine, without a significant tissue irritation.